Perception regarding needle stick and sharp injuries among clinical year medical students - Juni, Muhamad Hanafiah; M, Amir Aiman; A, Asma Nabilah; J. H., Ng; Wong, S.J.; Ibrahim, Faisal (Community Health Society Malaysia, 2015)
Introduction: Medical students are exposed to needle stick and sharp injuries (NSSIs) in their everyday routine whether in handling sharp medical instruments or contacting with patients. Thus, it is important to assess the perception of medical students regarding needle stick and sharp injuries, as it is an important feedback to medical school on the effectiveness of their teaching in reducing NSSIs. Objective: To determine the level of perception regarding NSSIs among clinical year’s medical students in a public university, and its association with the knowledge an attitude towards NSSIs. Materials and Methods: A cross sectional study was conducted among 320 clinical year’s medical students from a local public university in Malaysia. The respondents were selected according to the year of study by using stratified random sampling. The study was conducted in May and June 2011 for a period of two months. Self-administrated questionnaires were used in the study. The questionnaires were developed by researchers, and were pre-tested among nursing students in one of the local hospital. Results: Response rate was 93.8%, in which 300 out of 320 respondents were participating in the study. The result showed that 51% of respondents attained good level of perception regarding NSSIs. Meanwhile 53.3% achieved good level of attitude and 55.3% of the respondents attained good knowledge level towards NSSIs. The 5th year medical students got the highest level of perception (21%) on NSSIs as compared to 4th year (10%) and 3rd year (19.6%).There is significant association between level of perception and year of study (P= 0.002) as well as between level of perception and level of knowledge (P = 0.001) and attitude (P ˂ 0.001). Conclusion: Overall there were high proportion of clinical year medical students are having inappropriate perception, unsatisfactory knowledge and inappropriate attitude toward NSSIs. Knowledge and attitude regarding NSSIs showed significant association with perception toward NSSIs.